Variations of Infiltration and Electronic Contact in Mesoscopic Perovskite Solar Cells Revealed by High‐Resolution Multi‐Mapping Techniques - Tom O. Dunlop (Advanced Functional Materials, 2019)
A combination of high‐resolution mapping techniques is developed to probe the homogeneity and defects of mesoscopic perovskite solar cells. Three types of cells using a one‐step infiltration process with methylammonium lead iodide (MAPbI3) or 5‐ammoniumvaleric acid‐MAPbI3 solutions, or two‐step process with MAPbI3 solution are investigated. The correlation between photoluminescence, photocurrent, electroluminescence, and Raman maps gives a detailed understanding of the different infiltration mechanisms, electronic contact at interfaces, and effect on local photocurrent for the cells. The one‐step MAPbI3 cell has very limited infiltration of the perovskite solution which results in poor device performance. High loading of the mesopores of the TiO2 and ZrO2 scaffold is observed when using 5‐ammoniumvaleric acid, but some micrometer‐sized non‐infiltrated areas remain due to dense carbon flakes hindering perovskite infiltration. The two‐step cell has a complex morphology with features having either beneficial or detrimental effects on the local photocurrent. The results not only provide key insights to achieving better infiltration and homogeneity of the perovskite film in mesoporous devices but can also aid further work on planar devices to develop efficient extraction layers. Moreover, this multi‐mapping approach allows the correlation of the local photophysical properties of full perovskite devices, which would be challenging to obtain by other techniques.